Temperature distribution of T- joint friction stir welding - Aziz Hussein, Sadiq; Abdul Khader Al-Jumaili, Shaymaa; A. Mahmood, Raed (International Journal of Engineering and Technology, 2018)
Friction stir welding is a reliable welding method; it can be employed to join different structural configurations. Joint types such as lap, butt and T have been successfully produced by this welding method. In this study, a trial has been made to numerically simulate the heat generation and temperature distribution during the welding process of a T-joint. The workpieces materials were hardened 5052 and tempered 7075 Al Alloys, each material was investigated separately. Different rotational and welding speeds were used, besides, the pin length was also varied to accommodate the investigation of the top plate thickness effect. A visco-plastic finite element model was adopted to investigate the effect of parameters ranges on the temperature distribution. The results showed that the temperature distribution of T-joint depends mainly on the material to be welded and rotational speed. Besides, increasing the pin length from 7 to 10 mm could significantly increase the resulted temperature by approximately 14%. Therefore, the thickness of the upper plates of the T-joint plays a significant role on the resulted process temperature.Â Â